2015
DOI: 10.1111/dom.12480
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting or antagonizing glucagon: making progress in diabetes care

Abstract: Absolute or relative hyperglucagonaemia has been recognized for years in all experimental or clinical forms of diabetes. It has been suggested that excess secretion of glucagon by the islet α cells is a direct consequence of intra-islet insulin secretory defects. Recent studies have shown that knockout of the glucagon receptor or administration of a monoclonal specific glucagon receptor antibody make insulin-deficient type 1 diabetic rodents thrive without insulin. These observations suggest that glucagon play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 94 publications
0
32
0
2
Order By: Relevance
“…a-Cell hyperplasia has been raised as a potential concern with pharmacologic antagonism of glucagon action (28). Mice with homozygous disruption of the glucagon receptor gene develop dramatic elevations in plasma glucagon levels (.1,000-fold), hyperplasia of a-cells (29), and even neuroendocrine tumors (30).…”
Section: Discussionmentioning
confidence: 99%
“…a-Cell hyperplasia has been raised as a potential concern with pharmacologic antagonism of glucagon action (28). Mice with homozygous disruption of the glucagon receptor gene develop dramatic elevations in plasma glucagon levels (.1,000-fold), hyperplasia of a-cells (29), and even neuroendocrine tumors (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, antagonism of glucagon action in liver failed to prevent the ability of insulin to suppress HGP during hyperinsulinemic-euglycemic clamps in mice also lacking hepatic insulin signaling, indicating that peripheral actions of insulin to regulate HGP are independent of acute changes of liver glucagon signaling [37], consistent with older studies that show the extra-hepatic action of insulin suppresses HGP regardless of portal concentrations of glucagon [69]. Although insulin controls HGP independent of acute changes in glucagon, several clinical studies have demonstrated reductions in blood glucose levels with glucagon receptor antagonists [70]…”
Section: Extra-hepatic Control Of Hgpmentioning
confidence: 53%
“…A few recent studies have shown the efficacy of GLP-1 receptor (GLP-1R) agonists 57,58 and dipeptidyl peptidase-IV (DPP IV) inhibitors in these patients. It is possible that these two drugs are efficacious in the treatment of patients with PAX4 mutations, through their action on glucagon inhibition 59 .…”
Section: Paired Box Protein 4 Mody (Pax4 Mody; Mody 11)mentioning
confidence: 99%